A field experiment to assess barriers to accurate household food waste measurements - Merian, Sybilla; O'Sullivan, Kevin; Stöckli, Sabrina; Beretta, Claudio; Müller, Nadina; Tiefenbeck, Verena; Fleisch, Elgar; Natter, Martin (Resources Conservation and Recycling, 2024)
The United Nations’ sustainable development goals call for a 50 % reduction in global household food waste by 2030, but an accurate measurement method to quantify household food waste has yet to be developed. In a field experiment with 359 households, this study compares standard food waste measurement methods (survey, diary, kitchen caddy) and assesses the barriers to accurate measures. Based on our experimental design, we derive a minimal estimate of food waste (ground truth) that allows us to examine and explain the differences in the results of these methods. The results suggest that physical waste measurement is the most accurate measurement method, as it evokes the least behavioral adaptations. However, this method is resource-intensive and not always feasible. We provide guidance on how to measure food waste based on the purpose of the measurement, including specific materials to use and reporting standards to follow.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Biases; Diary; Household food waste measurement; Kitchen caddy; Survey; Underestimation